Pengaruh Suhu Penuangan Terhadap Kualitas Dan Cacat Coran Aluminium Bekas Kaleng Minuman Dengan Metode Lost Foam Casting - Tjiroso, Bambang; Umar, Kifli; Rais, Sandi; Rajak, Sahdar; Zulfikram, Zulfikram (Fakultas Teknik Universitas Khairun, 2024)
The purpose of this study is to determine the effect of pouring temperature on defect quality in aluminum castings for beverage cans, using the Lost Foam Casting method. The results indicate that pouring temperature significantly influences casting quality. Higher pouring temperatures improve casting quality by increasing fluidity, allowing the molten metal to better fill the mold cavities. Conversely, lower pouring temperatures reduce the aluminum's flowability. Observed defects primarily include cavities or small holes ranging in size from approximately 0.28000 µm to 0.6843 µm, suggesting porosity defects. Larger cavities (0.6843 µm) likely result from gas entrapment or shrinkage during cooling, while smaller cavities may be due to gas trapped on the surface of the castings.